2003
DOI: 10.1007/s00213-003-1462-6
|View full text |Cite
|
Sign up to set email alerts
|

Driving ability after acute and sub-chronic administration of levocetirizine and diphenhydramine: a randomized, double-blind, placebo-controlled trial

Abstract: In contrast to diphenhydramine, driving performance was not significantly affected while using 5 mg levocetirizine once daily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 37 publications
3
48
0
2
Order By: Relevance
“…Impairment was most pronounced after one-time administration; but after 4 to 5 days of administration, significant impairment had been shown for triprolidine, 8,10 clemastine, 15 and diphenhydramine. 13 However, the effects on driving performance after 4 to 5 days of administration are much less pronounced than after immediate administration, and some studies failed to find significant impairment after repeated administration of first-generation antihistamines such as triprolidine, 9,11 terfenadine, 7,10,12 and dexchlorpheniramine. 17 Nevertheless, after 4 to 5 days of treatment some subjects were unable to complete their driving tests, illustrating that sedative effects are not absent after repeated administration.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Impairment was most pronounced after one-time administration; but after 4 to 5 days of administration, significant impairment had been shown for triprolidine, 8,10 clemastine, 15 and diphenhydramine. 13 However, the effects on driving performance after 4 to 5 days of administration are much less pronounced than after immediate administration, and some studies failed to find significant impairment after repeated administration of first-generation antihistamines such as triprolidine, 9,11 terfenadine, 7,10,12 and dexchlorpheniramine. 17 Nevertheless, after 4 to 5 days of treatment some subjects were unable to complete their driving tests, illustrating that sedative effects are not absent after repeated administration.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on antihistamines and driving were not conducted in a mixed-sex population. With the exception of the levocetirizine study, 13,33 including 24 men and 24 women (they reported no sex differences for levocetirizine and diphenhydramine), the number of included subjects in studies with mixed-sex populations is too low to provide hard evidence on possible sex differences with sufficient statistical power. Nevertheless, results from these studies suggest that there are no significant sex differences for clemastine, 14,15 mizolastine, 14 and fexofenadine.…”
Section: Sex Effectsmentioning
confidence: 99%
See 3 more Smart Citations